Female Entrepreneurs Who Succeed in Male-Dominated Sectors in Ethiopia - Alibhai, Salman; Buehren, Niklas; Papineni, Sreelakshmi (World Bank, Washington, DC, 2016)
In developing countries, female entrepreneurs have low returns. Yet, the few women who cross over into traditionally male-dominated sectors double their profits. So why don't more women cross over? When parents and husbands support them, women are more likely to cross over. When they lack information on the earnings potential in male-dominated sectors, they are less likely to. This suggests a path to promote women entrepreneurs crossing over. The challenges Ethiopian women face in getting jobs and earning income come from a range of sources. Women start from a more difficult situation than men --without easy access to finance, land, training, education and effective business networks. The share of women in Ethiopia without education is almost twice that of men, which in turn limits women entrepreneurs' ability to grow their businesses. Reducing gender inequalities in education and the labor market could increase annual GDP growth in Ethiopia by around 1.9 percentage points.